Determinants of climate change adaptation strategies’ adoption among maize farming households: evidence from Malawi - Nkhoma, Sydney; Kapito, Lawrence Armando; Mainje, Michael (Frontiers in Climate, 2026)
IntroductionClimate change poses a serious threat to agricultural productivity and food security in Malawi, particularly among rural households that rely heavily on rainfed farming. This study examined the determinants of climate change adaptationv strategies among maize smallholder farmers in Chipoka EPA in Salima District, focusing on irrigation systems, zero tillage, and water harvesting.Data and methodsPrimary data were collected from 120 randomly selected households using a semi-structured questionnaire, and the multivariate probit model was employed to analyse factors influencing adoption.ResultsThe results revealed that being male, higher education level, landholding size, income, access to extension service and perceptions of changes in rainfall and temperature significantly and positively influenced the adoption of adaptation strategies. The findings underscore the importance of both socioeconomic, institutional and agroecological factors in shaping farmers’ adaptive responses.ConclusionThe study concludes that enhancing adaptive capacity requires policies that strengthen extension services, promote farmer training, address gender inequalities, and improve access to financial and land resources. Expanding irrigation and water harvesting systems, alongside reliable climate information services, is also essential. Collectively, these measures can increase resilience, improve agricultural productivity, and ensure sustainable food security among rural farming households in Malawi.